3D nitrogen-doped Ti3C2Tx/rGO foam with marco- and microporous structures for enhance supercapacitive performance. (1st February 2022) - Wu, Niandu; Zhao, Wenhua; Zhou, Boye; Wu, Yizhang; Hou, Wentao; Xu, Wei; Du, Jun; Zhong, Wei
Highlights: 3D NTG foam was synthesized via the multistep of gelation assisted with urea, freeze-casting, and annealing processes. The porous structures were adjusted by the decomposition of urea in the framework. The NTG foam shows a large surface area and rapid ion transfer. The NTG foam electrode exhibits excellent supercapacitance, rate performance and cycling stability. Abstract: Ti3 C2 Tx (MXene) has intriguing application potential for supercapacitors. However, it usually suffers from self-accumulate and restack, resulting in the decrease of electrochemical active sites and low capacitance. Here, we demonstrated a 3D nitrogen-doped Ti3 C2 Tx /rGO (NTG) foam which was synthesized through the multistep of gelation assisted with urea, freeze-drying, and thermal treatment processes. The decomposition of urea can not only change the morphology, bringing out more open marco- and microporous structures, but also improve the conductivity due to the nitrogen doping in the matrix. The 3D porous architecture can expose more electrochemical active sites, and thus accelerate the transport/diffusion of electrolyte ions. Consequently, the NTG foam possesses a high specific capacitance of 463 F g −1, good rate performance, and outstanding cycling stability (90.8% retention after 10 000 cycles) in H2 SO4 electrolyte, showing enhanced performance of supercapacitors in comparison with pure Ti3 C2 Tx and Ti3 C2 Tx /rGO electrode.